Efektifitas Strategi Promosi Pada Keputusan Pembelian Konsumen Kuliner Di Kota Solo Masa Pandemi Covid-19 - Fikrina Faraidi Fardani (Bulletin of Management and Business, 2021)
Covid-19 has caused the economy to decline, but people's consumption patterns have actually increased. During the PSBB period, people are limited in their activities outside the home. However, there are still many people who buy culinary products with a fairly high intensity, both online and offline. Culinary products greatly affect the existence due to Covid-19. Attractive marketing strategies such as promos and discounts are allegedly able to create consumers. The purpose of this study is to confirm that the promotional strategies carried out by culinary business people have been effective in influencing consumer purchasing decisions. This research is a descriptive study using a quantitative analysis approach. Sampling in this study used a convenience sampling technique. The number of research samples was 130 respondents. The results of data analysis show that even though income is decreasing, personal consumption for just "snacking" is still there and tends to be high. Purchase of culinary products online is mostly done through online services. The existence of a promotional strategy in the form of discounts is able to attract consumers to make purchases. One of the reasons consumers buy online is because they are lazy to leave the house and the many promos offered by culinary business.